1986
DOI: 10.1016/s0735-1097(86)80504-6
|View full text |Cite
|
Sign up to set email alerts
|

Infarct expansion: Pathologic analysis of 204 patients with a single myocardial infarct

Abstract: The reasons for the marked variability in expansion of myocardial infarcts are unknown. To examine this question, the hearts in 204 patients with a single myocardial infarct, autopsied at The Johns Hopkins Hospital and studied after coronary arteriography and fixation in distension, were reviewed. There were 58 (28%) hearts with marked infarct expansion, 34 (17%) with moderate expansion and 112 (55%) with no or minimal expansion. The degree of expansion was greater in larger, more transmural infarcts (p less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

1989
1989
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(58 citation statements)
references
References 11 publications
1
52
0
5
Order By: Relevance
“…The increase in %AWM observed for this subgroup was accounted for by increases in the extension subgroup. While the %AWM for the dilatation group did not significantly change (34.4±12.4% at entry versus 31.5±14.2% at 3 months), the %AWM for the extension group increased from 24 involved by AWM or enlargement of the total left ventricular surface area. Thus, to fully understand the natural history of these variables, it is necessary to quantitate their absolute and relative changes with a three-dimensional model of the ventricle.…”
Section: Infarct Groupsmentioning
confidence: 78%
“…The increase in %AWM observed for this subgroup was accounted for by increases in the extension subgroup. While the %AWM for the dilatation group did not significantly change (34.4±12.4% at entry versus 31.5±14.2% at 3 months), the %AWM for the extension group increased from 24 involved by AWM or enlargement of the total left ventricular surface area. Thus, to fully understand the natural history of these variables, it is necessary to quantitate their absolute and relative changes with a three-dimensional model of the ventricle.…”
Section: Infarct Groupsmentioning
confidence: 78%
“…A large autopsy series confirmed the association of infarct expansion with large transmural infarcts. 35 Infarct expansion occurred more frequently in the left anterior descending coronary artery than in the right coronary artery, and increased heart weight correlated inversely with expansion. Differences in regional wall thickness, the radius of curvature, and intramural tension also influence infarct expansion and remodeling.…”
Section: Infarct Artery Patencymentioning
confidence: 94%
“…Furthermore, LV volumes were more increased in LAD MI group, indicating more severe post-MI LV remodeling than in the LCx MI group. It has been shown that infarct expansion occurs predominantly in MI associated with the LAD (28). Therefore, the remodeling process is more intensified after LAD MI and thus recapitulates important characteristic of clinical HF development.…”
Section: Discussionmentioning
confidence: 95%